Genome-wide identification of sweet orange (Citrus sinensis) histone modification gene families and their expression analysis during the fruit development and fruit-blue mold infection process - Xu, Jidi; Xu, Haidan; Liu, Yuanlong; Wang, Xia; Xu, Qiang; Deng, Xiuxin (Frontiers in Plant Science, 2015)
In eukaryotes, histone acetylation and methylation have been known to be involved in regulating diverse developmental processes and plant defense. These histone modification events are controlled by a series of histone modification gene families. To date, there is no study regarding genome-wide characterization of histone modification related genes in citrus species. Based on the two recent sequenced sweet orange genome databases, a total of 136 CsHMs (Citrus sinensis histone modification genes), including 47 CsHMTs (histone methyltransferase genes), 23 CsHDMs (histone demethylase genes), 50 CsHATs (histone acetyltransferase genes), and 16 CsHDACs (histone deacetylase genes) were identified. These genes were categorized to 11 gene families. A comprehensive analysis of these 11 gene families was performed with chromosome locations, phylogenetic comparison, gene structures and conserved domain compositions of proteins. In order to gain an insight into the potential roles of these genes in citrus fruit development, 42 CsHMs with high mRNA abundance in fruit tissues were selected to further analyze their expression profiles at six stages of fruit development. Interestingly, a numbers of genes were expressed highly in flesh of ripening fruit and some of them showed the increasing expression levels along with the fruit development. Furthermore, we analyzed the expression patterns of all 136 CsHMs response to the infection of blue mold (Penicillium digitatum), which is the most devastating pathogen in citrus postharvest process. The results indicated that 20 of them showed the strong alterations of their expression levels during the fruit-pathogen infection. In conclusion, this study presents a comprehensive analysis of the histone modification gene families in sweet orange and further elucidates their behaviors during the fruit development and the blue mold infection responses.